Suicide among young persons: causes, symptoms and intervention strategies - Mott, Cora (My University, 1984)
The statistics, causes, symptoms, methods used, intervention and prevention strategies were researched. Research showed there has been an alarming increase in suicide among the young persons in the United States. Research was analyzed to find facts and strategies that would enable school personnel, family members and the community as a whole to improve the environment of the young people so more lives could be saved from suicide. Results support a conclusion that suicide can be decreased with the help of a caring public, school personnel and family members.
Keywords: Suicide -- Prevention; Youth -- Suicidal behavior